Knowledge building and vocabulary growth: Assessing the impact of seamless Chinese vocabulary learning for international students. - Xiaosheng Zhou; Ying Soon Goh (PLoS ONE)
This study investigates the effectiveness of Seamless Chinese Vocabulary Learning (SCVL) among international students learning Chinese as a Foreign Language (CFL) to foster vocabulary knowledge building. A new theoretical framework of SCVL was introduced and validated to guide this exploration. The research involved 32 international students enrolled in a Chinese university. Data collection included Chinese Lexical Frequency Profile (LFP) were at HSK Level 4, a SCVL questionnaire, and semi-structured interviews. The findings indicate that SCVL significantly enhances students' HSK Level 4 vocabulary learning and retention across diverse performance groups over time, while also providing a positive and engaging learning experience. SCVL creates an authentic and repetition-enabled learning context, fostering higher levels of interaction and multi-modal, immediate, and learner-friendly scaffolding. Moreover, the study reveals that SCVL motivates students to actively participate in vocabulary acquisition, despite facing certain challenges. By incorporating the SCVL framework, language instructors can enhance their pedagogical practices and promote sustainable language learning outcomes. Future research is recommended to include a broader range of learners with diverse backgrounds and language proficiency levels, as well as to compare seamless learning with traditional learning approaches. Additionally, exploring CFL teachers' perceptions of SCVL would be valuable to further understand its impact on language instruction.